Resistance and Postcolonialism: A Critical Review - Bhandari, Nagendra Bahadur (Journal of Political Science, 2022)
This article makes a brief review of the models of resistance in postcolonial discourses and practices. There are mainly four models of resistance. The first model of resistance focuses on rewriting colonial narratives by subverting the negative image of colonized people and culture. In this model, the writers and theories involve in literary activities of reading and rewriting to the colonial discourse to create a positive image of colonized people and country. The second model emphasizes cultural negotiation and the formation of human subjectivities. This model focuses on cultural encounters of the colonizer and colonized in the hybrid space which undermines the total domination of the colonial power. These cultural encounters render hybrid subjectivities of colonized subjects. The third model takes a radical stance. This model advocates the struggle even using violent methods against colonial authority for the liberation of the colonized. Going beyond simply resisting the colonial authority, the fourth model of resistance emphasizes on subverting the colonial power and transforming the material condition and social relationship of colonized people. This transformative model of resistance remains relevant even in other movements of social justice to change the situation of the marginalized group.